Preferential oxidation of CO on Ni/CeO2 catalysts in the presence of excess H-2 and CO2 - Malwadkar, Sachin S.; Bera, Parthasarathi; Hegde, M. S.; Satyanarayana, C. V. V. (Reaction Kinetics Mechanisms and Catalysis, 2012)
Preferential oxidation of CO (CO-PROX) was carried out over Ni supported on CeO2 prepared by the co-precipitation method. The influence of metal loadings (2.5, 5 and 10 wt.% Ni) and the reaction conditions such as reaction temperature and feed composition on CO oxidation and oxidation selectivity were evaluated by using dry reformate gas. No other reactions like CO or CO2 methanation, coking, reverse water gas shift (RWGS) reaction is observed in the temperature range of 100-200 A degrees C on these catalysts. Hydrogen oxidation dominates over CO oxidation above the temperature of 200 A degrees C. An increase in oxygen leads to an increase in CO conversion but a simultaneous decrease in the O-2 selectivity. It has been noticed that 5 and 10 % Ni/CeO2 show better catalytic activity towards CO-PROX reaction. These catalysts were characterized by S-BET, XRD, TEM, XPS and H-2-TPR.
Keywords: CeO2; CO-PROX; fuel cells; Methanation; Ni